Conflitos discursivos nos ditos de professores/as de ciências sobre sexualidade - Tayline Silva de Oliveira (2018)
The way sexuality has been lived, what has been told about it and who speaks about it, points to some peculiarities on each culture throughout the history. And this is because there are an amount of discourses which deal with nominating, describing, metaphorizing, explaining and judging the sexuality. Thus, there is not a regular and unique discourse about sexuality. In this dissertation I operate with some Foucaults concepts, such as discourse, power relations, subject position and I took as object the discourses which are assumed and spread by science teachers. I identify, describe and analyze the elements of feminist, male chauvinist and Queer discourses that are present on sayings of these teachers, about sexuality; the power relations which are established and some subject positions that are demanded on these discourses. The current dissertation is inserted on post critical studies area, in which sexuality in considered a historical dispositive and the concepts of body, sex and gender are thought as social and cultural constructs. As methodology procedures, I interviewed ten science teachers from Belo Horizonte Municipal Education Network and, then, I used the discourse analysis with inspiration on Michel Foucault. Thus, the general argument which is defended on this dissertation is that feminist, male chauvinist and Queer discourses act for the comprehension that science teachers have about sexuality. Moreover, these discourses demand some subject positions to be assumed by those teachers. I also show, through the analysis, that feminist and male chauvinist discourses, present on teachers sayings, are concurrent, and Queer and male chauvinist discourses are also concurrent and conflicting between themselves. However, the feminist and Queer discourses are as complementary as concurrent. This analysis shows that, on one hand, in spite of the historical struggles accumulated by feminist movements, for equal rights, the male chauvinist discourse still remains among science teachers. On the other hand, it was possible to verify that feminist discourse came out too strongly on science teachers sayings about sexuality. Besides, Queer discourse, which struggles for rights of groups which are excluded from power exercises, and that problematizes gender and sexuality fixed identities, is also present on the sayings of science teachers from basic education